Legal Protection for The Indigenous Law Communities and Their Traditional Rights Based on the Verdict of the Constitutional Court - Putera Astomo; Asrullah Asrullah (Faculty of Law, Universitas Padjadjaran, 2019)
AbstractThis study covers the problems related to the regulation of Adat (Indigenous) law communities. First, the Law Number 41 of 1999 on Forestry categorizes indigenous forests as State Forest. Therefore, the state has the authority to stipulate indigenous forests as long as the relevant Indigenous Law Communities are still existed and recognized. Second, the Law Number 27 of 2007 on Management of Coastal Areas and Small Islands provides opportunities for owners of large capital through Coastal Water Concession Rights (HP-3), but the substance does not provide space for coastal communities especially fishermen carrying out economic activities in coastal areas. Due to limited capital and technology, coastal communities are not able to compete with large capital owners hence the poverty level of fishermen keeps increasing. Finally, the Law Number 41 of 1999 on Forestry and the Law Number 27 of 2007 on Management of Small Coastal Areas and Islands tested materially to the Constitutional Court. The research method used in this study is normative legal research. The results of the research are forms of legal protection against the existence of indigenous law communities and their traditional rights, which include protection of their indigenous rights over the status and management of indigenous forests and their protection over the management of coastal areas and small islands.Perlindungan Hukum terhadap Hak Tradisional Masyarakat Adat berdasarkan Putusan Mahkamah KonstitusiAbstrakMasalah-masalah yang berhubungan dengan pengaturan kesatuan masyarakat hukum adat. Pertama, status Hutan Adat termasuk kategori Hutan Negara sebagaimana diatur dalam UU No. 41 Tahun 1999 tentang Kehutanan di mana negara berwenang menetapkan hutan adat sepanjang menurut kenyataannya masyarakat hukum adat yang bersangkutan masih ada dan diakui keberadaannya. Kedua, UU No. 27 Tahun 2007 tentang Pengelolaan Wilayah Pesisir dan Pulau-Pulau Kecil memberikan kesempatan kepada pemilik modal besar melalui Hak Pengusahaan Perairan Pesisir (HP-3) tetapi substansinya tidak memberikan ruang bagi masyarakat pesisir khususnya nelayan melakukan aktivitas ekonomi di wilayah pesisir. Masyarakat pesisir karena keterbatasan modal dan teknologi tidak mampu bersaing dengan pemilik modal besar akhirnya tingkat kemiskinan nelayan semakin meningkat. Akhirnya UU No. 41 Tahun 1999 tentang Kehutanan dan UU No. 27 Tahun 2007 tentang Pengelolaan Wilayah Pesisir dan Pulau-Pulau Kecil diuji material ke Mahkamah Konstitusi. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif. Hasil penelitiannya adalah bentuk perlindungan hukum terhadap eksistensi kesatuan masyarakat hukum adat dan hak-hak tradisionalnya meliputi: perlindungan terhadap hak ulayat kesatuan masyarakat hukum adat atas status dan pengelolaan hutan adat serta perlindungan terhadap kesatuan masyarakat hukum adat atas pengelolaan wilayah pesisir dan pulau-pulau kecil.DOI: https://doi.org/10.22304/pjih.v6n1.a5